Analyzing the Turkish Translations of Proper Nouns in The Scottish Fairy Book Using Van Coillie’s Model - Dolunay Kumlu (İstanbul Üniversitesi Çeviribilim Dergisi)
Fairy tales are anonymous verbal works of folk literature. They are transferred from a generation to another by narration and in this way transfer the culture of the society in which they were created to successive generations. Fairy tales are embellished with extraordinary plots, extraordinary characters, and imagination and are sometimes published and become written literary works, thus increasing the permanence of fairy tales. Fairy tales can be transmitted to wider masses only by being translated. This article researches the book The Scottish Fairy Book compiled by Scottish author Elizabeth Wilson Grierson and İskoç Masalları as the Turkish translation of this literary work translated by Derya Işık. The aim of this research is to demonstrate and illustrate on the basis of a theoretical framework the strategies the translator pursued while translating the fairy tale compilation.Literary works have different perspectives for translating proper nouns. This study examines the views and strategies suggested by Van Coillie (2014) and his contemporary model of analysis for translating proper nouns in literary works in order to reveal the translator’s motives behind her decisions and preferences.